Effect of Non-ionic Surfactant (Triton X-100) on the Spectrophotometric Determination of Lead(II) with Potassium Benzyl Xanthate - Sreenivasa Rao, Battula; Shankar Dube, Som; Nagendrakumar, A.V.D.; Srinivasa Reddy, B. (Asian Journal of Chemistry, 2010)
The effect of non-ionic surfactant (Triton X-100) on the sensitive, simple and inexpensive spectrophotometric method was developed for the determination of lead(II) with potassium benzyl xanthate (KBX). Lead was complexed with potassium benzyl xanthate in presence of non-ionic surfactant (Triton X-100). Absorption spectrum of Pb(KBX)2 complex in the presence of nonionic surfactant medium shows a peak at 370 nm. The molar absorptivity of the complex was 6.723 × 104 dm3 mol-1 cm-1 and Sandell's sensitivity was 3.2478 × 10-3 mg cm-2. The system obeys Beer's law in the concentration range of 0.25 to 10.0 ppm. The composition of the complex (metal:ligand) was 1:2. The method was employed for the determination of lead in industrial effluents and ground water samples.